2009
DOI: 10.1016/j.physleta.2008.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Analytical analysis of the “collapse-revival” effect in the Jaynes–Cummings model

Abstract: The evolution of the atomic state population in a two-level system coupled to a single-mode quantum field is calculated in the analytical form. Essential characteristics of the "collapse-revival" effect are expressed in terms of the physical parameters of the system by means of simple formulas in both the resonant and the non-resonant cases. The obtained results are of great importance for the qualitative analysis of the phenomenon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…This effect was predicted theoretically [17] and later observed experimentally [18]. Its qualitative explanation and analytical description was also given by [19][20][21]. It was shown that the evolution of the population of the atomic states is characterized by two time scales.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…This effect was predicted theoretically [17] and later observed experimentally [18]. Its qualitative explanation and analytical description was also given by [19][20][21]. It was shown that the evolution of the population of the atomic states is characterized by two time scales.…”
Section: Introductionmentioning
confidence: 64%
“…This gives the possibility of changing the summation over n to an integration over the complex variable. Then this integral in the complex plane can be evaluated using the same approach as in [19]. This approach is based on the saddle point method [27].…”
Section: Electron Spin Dynamics In a Single-mode Quantized Fieldmentioning
confidence: 99%
“…The Rabi oscillations of a two-level atom in a resonant, single-mode coherent field state is one of the simplest phenomena in quantum optics. Nevertheless, it exhibits surprisingly complex features at the mesoscopic scale (few tens of photons) [1][2][3][4]. The oscillations, at an angular frequency Ω 0 √ n, collapse and revive (n is the average photon number in the coherent state; Ω 0 is the vacuum Rabi frequency measuring the atom-field coupling).…”
mentioning
confidence: 99%
“…The cavity C, cooled down to 1.5 K by a wet 4 He cryostat, sustains a linearly polarized Gaussian standingwave mode with a waist w = 6 mm [3]. Its damping time is T Cav = 8.1 ± 0.3 ms. Its temperature corresponds to an average thermal photon number n th = 0.38.…”
mentioning
confidence: 99%
“…It is noteworthy that analogous quasiintersections, higher order resonances (u k ≈ k/f), will arise according to the structure of the accurate solution of the JCM [8,9] as the field amplitude is increased further. However, an analysis of the temporal problem with arbitrary field amplitudes even within the framework of the literature approach [12] is fraught with rather tedious numerical calculations and will be reported separately. We will limit ourselves within the scope of the present work to an analytical investigation based on Eq.…”
mentioning
confidence: 99%